Nematocystis indicus sp. nov. (Apicomplexa: Monocystidae) from an Indian earthworm (Annelida: Oligochaeta) Perionyx excavatus (Perrier) - Bandyopadhyay, Probir K.; Mitra, Amlan K.; Bhowmik, Biplab (Zootaxa, 2006)
A bio-diversity study in search of acephaline gregarines from Sandeshkhali village under Sundarban delta of West Bengal province, India revealed a new species of Nematocystis Hessé, 1909; Nematocystis indicus sp. nov. in the seminal vesicles of earthworms Perionyx excavatus (Perrier). Gamonts are elongated, with a cylindrical main body and a short wider anterior portion that contains the small nucleus. Both the ends are gradually narrowed like a ‘V’ to a nearly pointed tip.  Body length varies from 172.0–400.0 µm (mean= 257.0 ± 65.4 µm). The maximum body width ranges from 18.0–49.0 µm (mean= 25.0± 9.0). Gametocyst almost rounded ranging from 48.0–68.0 µm (mean= 56.0 ± 1.3 µm). Oocysts biconical, measuring 7.0–11.5 (mean= 9.3 ± 1.1 µm)